IMPACT OF ALCOHOL ON RAT HEART AND ENDOTHELIAL CELLULAR NITRIC OXIDE SYNTHASE ACTIVITY IN VITRO AND IN VIVO - DR. M. YUGANDHAR; M. RAJESWARA RAO (International Journal of Pharma and Bio Sciences, 2014)
Nitric oxide (NO) has been implicated in the regulation of heart contractility, platelet aggregation in the cardio vascular system of mammals. Multiple authors reported alcohol as to interact with cardio vascular NO pathway parameters. The impact of 20% ethanol (w/v) at selected doses of 5gm/per kg over 5 or 10 weeks in vivo and 100-1000 μ litre in vitro on the heart and endothelial (ET) cellular nitric oxide synthase (NOS) activity was reported. Alcohol at the employed doses in both in vitro and in vivo appeared to inhibit the rat heart and ET cellular 100000 x g soluble fractions NOS activity and this was reported as due to interaction of alcohol with rat heart and ET cellular based calcium / Calmodulin – dependent events on which NOS activity is known to be dependent.